Cyclic behavior and energy approach of the fatigue of shape memory alloys - Moumni, Ziad; Zaki, Wael; Maitournam, Habibou (Vietnam Journal of Mechanics, 2009)
This paper presents an energy-based low-cycle fatigue criterion that can be used in analyzing and designing structures made from shape memory alloys (SMAs) subjected to cyclic loading. Experimentally, a response similar to plastic shakedown is observed: during the first cycles the stress-strain curve shows a hysteresis loop which evolves during the first few cycles before stabilizing. By adopting an analogy with plastic fatigue, it is shown that the dissipated energy of the stabilized cycle is a relevant parameter for estimating the number of cycles to failure of such materials. Following these observations, we provide an application of the cyclic model, previously developed by the authors within the framework of generalized standard materials with internal constraints [16], in order to evaluate such parameter. Numerical simulations are presented along with a validation against experimental data in case of cyclic superelasticity.